Fog Computing - A Rasperry Pi Decentralized Network (Journal of Information Technology and Digital World, 2020)
Ever since the concept of parallel processing and remote computation became feasible, Cloud computing is at its highest peak in its popularity. Although cloud computing is effective and feasible in its usage, using the cloud for frequent operations may not be the be the most optimal solution. Hence the concept of FOG proves to be more optimal and efficient. In this paper, we propose a solution by improving the FOG computing concept of decentralization by implementing a secure distributed files system utilizing the IPFS and the Ethereum Blockchain technology. Our proposed system has proved to be efficient by successfully distributing the data in a Raspberry Pi network. The outcome of this work will assist FOG architects in implementing this system in their infrastructure and also prove to be effective for IoT developers in implementing a Raspberry Pi decentralized network while providing more security to the data.
Keywords: FOG Computing; Decentralized Application; data distribution; Blockchain; IPFS; Ethereum; smart contract; Truffle; Metamask; Raspberry Pi